PROSPEK PENGEMBANGAN KEBUN BURU RUSA PERUM PERHUTANI BKPH JONGGOL JAWA BARAT BERDASARKAN TINJAUAN EKOLOGI - Yanto Santosa; . Firmansyah (Institut Pertanian Bogor, 2012)
One form of sustainable wildlife utilization with ecological and economic values is game hunting. Due to game hunting’s promising prospects, Perum Perhutani planned to develop their deer captive breeding area (PRJ) into a hunting garden. The objective of this research was to study the prospects of deer captive breeding area of Perum Perhutani BKPH Jonggol, West Java into a hunting garden based on ecological considerations. The research was conducted in 2006. Based on direct observation, interviews with the locals and local officers, and observation of land cover change due to increase in population, it was concluded that Block 9 was the most ideal site for hunting garden due to its varied slopes which was preferred by deers, ideal land coverages such as grassland, shrubs and plantation forest, lack of enclave, abundant grazing area and accessible by the hunters. Based on land topography and land coverage, the most suitable hunting method for Block 9 was stalking. According to the Directorate General of PHPA (1988), the only weapon allowed for game hunting is firearm. Based on calculations and literature reviews, the maximum number of hunters allowed in Block 9 is 108 hunters per year with a hunting season of two months, during July and October. Assuming 100% hunting success with maximum number of hunters allowed, the hunting quota would be 108 deer per year. Further studies are required to determine the number of initial population to be introduced to the hunting area and time to start hunting activities, as well as prospects of PRJ development as hunting garden based on socio-economic considerations.